PDEODE Strategy Assisted by GeoGebra: Improving Students' Critical Thinking and Mathematical Analysis - Lailia Aini Rohmah; Bambang Sri Anggoro; Wawan Gunawan (Online Learning In Educational Research (OLER), 2023)
This study aimed to determine the effect of the PDEODE learning strategy on students' critical thinking and mathematical analysis skills. This research is quantitative research with a quasi-Experimental posttest-only control group design. The population of this study was all students of the eighth grade of MTs Negeri 2 Bandar Lampung, with a total population of 256 students. The sampling technique employed was cluster random sampling. The data analysis techniques performed were the normality test and the homogeneity test. The hypothesis testing performed was a Multivariate Analysis of Variance (MANOVA) test. Based on the results of research and the MANOVA test, the PDEODE learning strategy assisted by the GeoGebra application has an effect on students critical thinking and mathematical analysis skills. Further research is recommended to use the PDEODE strategy and GeoGebra media.